MEMBANGUN EKOSISTEM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS SEKOLAH, PERGURUAN TINGGI DAN KOMUNITAS DI KOTA SUKABUMI - Syalwa Elia Rahmawati; MULYAWAN SAFWANDY NUGRAHAN (CV. Adiba Aisha Amira, 2026)
The development of Islamic Religious Education (IRE) learning faces complex challenges that require integrated and sustainable collaboration across educational institutions. Fragmented IRE practices have limited the synergy between academic reinforcement, classroom implementation, and teacher professional development. This study aims to analyze collaboration patterns among schools, higher education institutions, and IRE teacher communities in building a learning ecosystem in Sukabumi City, as well as to identify actors’ roles, challenges, and development opportunities.This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews with three key informants, including an IRE teacher, an IRE supervisor, and the head of a postgraduate IRE program. The findings indicate that collaboration is perceived as an integrative learning ecosystem, where schools function as implementation sites, universities provide academic reinforcement, and teacher communities act as sustainability connectors. Although the implementation of collaboration remains partial and not fully institutionalized, it contributes to improving teacher professionalism and the quality of IRE learning. The study oncludes that sustainable collaboration requires role clarity, policy support, and strengthened institutional networks. The implications highlight the importance of developing a systematic and contextual collaborative model to enhance IRE learning and professional practice in schools.